PENGARUH PEMASARAN JEJARING MEDIA SOSIAL TERHADAP NIAT BELI KONSUMEN (Survei pada Mahasiswa STIE Wikara) - Asep Munawar; Suryana Suryana; Ratih Hurriyati (Jurnal Ekonomi dan Kebijakan Publik Indonesia, 2020)
Abstract        This study aims to examine the effect of marketing social media networks on consumer purchase intentions, the research method used is a survey with a quantitative approach, using a sample of 70 STIE Wikara students. The data analysis technique used is Linear Regression Analysis. The results showed that social media network marketing has a significant effect on consumer purchase intentions, or has a significant role on consumers' decisions to buy a product, other findings indicate that social media network marketing is related to consumer purchase intentions, where consumer involvement acts in influencing users social media to have consumer purchase intentions. This study reinforces that marketers must respond to the importance of increasing use of social media because it has a strong influence on consumer purchase intentions.